2016
DOI: 10.1039/c5cp03338a
|View full text |Cite
|
Sign up to set email alerts
|

Amylin–Aβ oligomers at atomic resolution using molecular dynamics simulations: a link between Type 2 diabetes and Alzheimer's disease

Abstract: Clinical studies identified Type 2 diabetes (T2D) as a risk factor of Alzheimer's disease (AD). One of the potential mechanisms that link T2D and AD is the loss of cells associated with degenerative changes. Amylin1-37 aggregates (the pathological species in T2D) were found to be co-localized with those of Aβ1-42 (the pathological species in AD) to form the Amylin1-37-Aβ1-42 plaques, promoting aggregation and thus contributing to the etiology of AD. However, the mechanisms by which Amylin1-37 co-aggregate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 70 publications
1
119
0
1
Order By: Relevance
“…Previous evidences suggested that Aβ 1‐42 played a critical role in the pathogenesis of AD, but the underlying mechanisms remained unknown. A lot of studies have supported that melatonin prevents the death of injured neurons in the hippocampus and cortex and improves the cognitive function of brain .…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidences suggested that Aβ 1‐42 played a critical role in the pathogenesis of AD, but the underlying mechanisms remained unknown. A lot of studies have supported that melatonin prevents the death of injured neurons in the hippocampus and cortex and improves the cognitive function of brain .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that interactions between different amyloid proteins and peptides may play a critical role in amyloid diseases (e.g., Aβ–tau 42 , tau-synuclein 43 , Aβ–transthyretin 44 , and IAPP–Aβ 45 ). For example, T2D has been identified as a major risk factor for AD 4648 and thus the co-aggregation of IAPP and Aβ may contribute to the cross-talk between these two diseases 49,50 . Therefore, we also investigate in our simulations the co-aggregation between Aβ16–22 and IAPP22–28, experimentally identified as the hotspot regions for the inter-molecular interaction between full-length Aβ and IAPP 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐amyloid interactions and coaggregation of peptides into heteropolymeric amyloid fibrils occur in disease‐causing proteins including amylin and amyloid‐β, amylin and α‐synuclein, amyloid‐β and α‐synuclein, and the tau protein and amyloid‐β . The interactions and mechanisms of coaggregation between these proteins have been difficult to investigate due to a lack of atomic resolution structures, although molecular dynamics simulations are proving highly useful and have revealed how these proteins interact with each other as well as the synergistic effects of cross‐amyloid interactions in altering the secondary structures of coaggregated proteins.…”
Section: Introductionmentioning
confidence: 99%